2014
DOI: 10.1068/i0679sas
|View full text |Cite
|
Sign up to set email alerts
|

Troxler Fading, Eye Movements, and Retinal Ganglion Cell Properties

Abstract: We present four movies demonstrating the effect of flicker and blur on the magnitude and speed of adaptation for foveal and peripheral vision along the three color axes that isolate retinal ganglion cells projecting to magno, parvo, and konio layers of the LGN. The demonstrations support the eye movement hypothesis for Troxler fading for brightness and color, and demonstrate the effects of flicker and blur on adaptation of each class of retinal ganglion cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Second, saccadic suppression (Bridgeman et al 1975) limits the communication of visual data through the visual system during self-generated eye movements, suggesting that it is the data garnered during fixations that are used to constrain perceptual inference. Third, the importance of foveation is illustrated in psychophysical data investigating the relationship between stimulus eccentricity and fading (Lou 1999; Bachy and Zaidi 2014). Faster fading of more eccentric stimuli implies that the choice of fixation location is important and is consistent with the reduced precision associated with data from the retinal periphery relative to the fovea.…”
Section: Discussionmentioning
confidence: 99%
“…Second, saccadic suppression (Bridgeman et al 1975) limits the communication of visual data through the visual system during self-generated eye movements, suggesting that it is the data garnered during fixations that are used to constrain perceptual inference. Third, the importance of foveation is illustrated in psychophysical data investigating the relationship between stimulus eccentricity and fading (Lou 1999; Bachy and Zaidi 2014). Faster fading of more eccentric stimuli implies that the choice of fixation location is important and is consistent with the reduced precision associated with data from the retinal periphery relative to the fovea.…”
Section: Discussionmentioning
confidence: 99%
“…This weak short-term adaptation might be easily counteracted by the dramatic changes that accompany saccades, for example by the motion streaks caused by the rapid movement of the eyes ( Burr and Ross, 1982 ), which may be so disruptive that they are suppressed (to some extent probably actively) from conscious perception (for reviews, see Ross et al, 2001 ; Ibbotson and Krekelberg, 2011 ; Binda and Morrone, 2018 ). Indeed, the retinal input caused by a saccade-like motion has been shown to strongly alter spiking activity of retinal ganglion cells (e.g., Roska and Werblin, 2003 ; Idrees et al, 2020 ), and it is known that simple on-and-off flashing of a stimulus (attempting to imitate the effect of saccades) can delay its perceptual fading ( Cornsweet, 1956 ; Bachy and Zaidi, 2014 ). However, it has been shown that unnaturally long adaptation (≥3 s) can survive a saccade and influence perception in humans (e.g., Melcher, 2005 ; 2007 ; Knapen et al, 2010 ; He et al, 2018 ) and that more natural short-term adaptation can attenuate contrast sensitivity and V1 activity across saccades in macaque monkeys ( Gawne and Woods, 2003 ; Niemeyer and Paradiso, 2017 ).…”
Section: Introductionmentioning
confidence: 99%